2008
DOI: 10.1007/s10719-008-9175-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel oligosaccharide has suppressive activity against human leukemia cell proliferation

Abstract: Various oligosaccharides containing galactose(s) and one glucosamine (or N-acetylglucosamine) residues with β1-4, α1-6 and β1-6 glycosidic bond were synthesized; Galβ1-4GlcNH 2 , Galα1-6GlcNH 2 , Galα1-6GlcNAc, Galβ1-6GlcNH 2 , Galβ1-4Galβ1-4GlcNH 2 and Galβ1-4Galβ1-4GlcNAc. Galα1-6GlcNH 2 (MelNH 2 ) and glucosamine (GlcNH 2 ) had a suppressive effect on the proliferation of K562 cells, but none of the other saccharides tested containing GlcNAc showed this effect. On the other hand, the proliferation of the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We previously reported that GlcNH 2 at 5 mM significantly ( P < 0.01) suppressed the growth of human K562 leukemia cells and human HUC-F2 (non-transformed) cells, whereas MelNH 2 at 5 mM significantly ( P < 0.01) suppressed the cell growth of K562 cells but not of HUC-F2 cells, as assessed at day 3 after exposure [ 26 ]. This suggests that GlcNH 2 is toxic to both tumor cells and non-transformed cells, whereas MelNH 2 is toxic to tumor cells but not to non-transformed cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that GlcNH 2 at 5 mM significantly ( P < 0.01) suppressed the growth of human K562 leukemia cells and human HUC-F2 (non-transformed) cells, whereas MelNH 2 at 5 mM significantly ( P < 0.01) suppressed the cell growth of K562 cells but not of HUC-F2 cells, as assessed at day 3 after exposure [ 26 ]. This suggests that GlcNH 2 is toxic to both tumor cells and non-transformed cells, whereas MelNH 2 is toxic to tumor cells but not to non-transformed cells.…”
Section: Resultsmentioning
confidence: 99%
“…Jurkat cells were maintained at 37 °C (5% CO 2 ) in tissue-culture dishes containing RPMI 1640 growth medium supplemented with 10% (v/v) fetal bovine serum, 25 μg/mL penicillin, and 50 μg/mL streptomycin. MelNH 2 was synthesized as described previously [ 26 ], and GlcNH 2 was purchased from Sigma (St. Louis, MO); these compounds were each dissolved in phosphate-buffered saline (pH 7.4) as 0.1 M solutions, sterilized through a 0.45-μm filter, and stored at −20 °C until use. Phorbol 12-myristate 13-acetate (PMA) and ionomycin (IM) were obtained from Sigma, and CsA was purchased from Calbiochem (San Diego, CA), and these compounds were stored as 1, 0.5, and 0.5 mM stock solutions, respectively, in dimethyl sulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6) and b-(1 ? 6) glycosidic bonds suppressed the proliferation of human leukemia K562 cells (Hosomi et al 2009). Iwata et al (2005) investigated the effects of chitosan oligosaccharides on the femur trabecular structure in ovariectomized rats by three-dimensional imaging analysis using micro-computed tomography (CT).…”
Section: Industrial Applications Of Oligosaccharidesmentioning
confidence: 99%